Prove
∑k=0n(nk)(2kk)(−12)k={12n(nn/2),n is even0,n is odd\displaystyle \sum_{k=0}^n{\binom{n}{k} \binom{2k}{k} {\left(\frac{-1}{2}\right)}^k} = \begin{cases} \frac{1}{2^n}\binom{n}{n/2}, & \text{n is even} \\ 0, & \text{n is odd} \end{cases}k=0∑n(kn)(k2k)(2−1)k={2n1(n/2n),0,n is evenn is odd
Note by Kartik Sharma 4 years ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Since (2kk) = 12π∫−ππe−ikt(1+eit)2k dt = 12π∫−ππ(2cos12kt)2k dt {2k \choose k} \; = \; \frac{1}{2\pi}\int_{-\pi}^\pi e^{-ikt}(1 + e^{it})^{2k}\,dt \; = \; \frac{1}{2\pi}\int_{-\pi}^\pi \big(2\cos\tfrac12kt\big)^{2k}\,dt (k2k)=2π1∫−ππe−ikt(1+eit)2kdt=2π1∫−ππ(2cos21kt)2kdt we have ∑k=0n(nk)(2kk)(−12)k=12π∫−ππ(nk)(2cos12kt)2k(−12)k dt=12π∫−ππ(1−2cos212kt)n dt = (−1)n2π∫−ππcosnt dt=(−1)n2n+1π∫−ππ(eit+e−it)n dt = (−1)n2n+1π∑k=0n(nk)∫−ππei(2k−n)t dt={12n(n12n)n even0n odd\begin{aligned} \sum_{k=0}^n {n \choose k}{2k \choose k}\big(-\tfrac12\big)^k & = \frac{1}{2\pi}\int_{-\pi}^\pi {n \choose k}\big(2\cos\tfrac12kt\big)^{2k} \big(-\tfrac12\big)^k\,dt \\ & = \frac{1}{2\pi}\int_{-\pi}^\pi \Big(1 - 2\cos^2\tfrac12kt\Big)^n\,dt \; = \; \frac{(-1)^n}{2\pi}\int_{-\pi}^\pi \cos^nt\,dt \\ & = \frac{(-1)^n}{2^{n+1}\pi}\int_{-\pi}^\pi \big(e^{it} + e^{-it}\big)^n\,dt \; = \; \frac{(-1)^n}{2^{n+1}\pi}\sum_{k=0}^n {n \choose k} \int_{-\pi}^{\pi} e^{i(2k-n)t}\,dt \\ & = \left\{ \begin{array}{lll} \frac1{2^n}{n \choose \frac12n} & \hspace{1cm} & n \mbox{ even} \\ 0 & & n \mbox{ odd} \end{array} \right. \end{aligned} k=0∑n(kn)(k2k)(−21)k=2π1∫−ππ(kn)(2cos21kt)2k(−21)kdt=2π1∫−ππ(1−2cos221kt)ndt=2π(−1)n∫−ππcosntdt=2n+1π(−1)n∫−ππ(eit+e−it)ndt=2n+1π(−1)nk=0∑n(kn)∫−ππei(2k−n)tdt={2n1(21nn)0n evenn odd
Try this one
@Mark Hennings
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Since (k2k)=2π1∫−ππe−ikt(1+eit)2kdt=2π1∫−ππ(2cos21kt)2kdt we have k=0∑n(kn)(k2k)(−21)k=2π1∫−ππ(kn)(2cos21kt)2k(−21)kdt=2π1∫−ππ(1−2cos221kt)ndt=2π(−1)n∫−ππcosntdt=2n+1π(−1)n∫−ππ(eit+e−it)ndt=2n+1π(−1)nk=0∑n(kn)∫−ππei(2k−n)tdt={2n1(21nn)0n evenn odd
Try this one
@Mark Hennings